2020
DOI: 10.1093/mnras/staa3625
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum of halo intrinsic alignments in simulations

Abstract: We use a suite of N-body simulations to study intrinsic alignments (IA) of halo shapes with the surrounding large-scale structure in the ΛCDM model. For this purpose, we develop a novel method to measure multipole moments of the three-dimensional power spectrum of the E-mode field of halo shapes with the matter/halo distribution, $P_{\delta E}^{(\ell )}(k)$ (or $P^{(\ell )}_{{\rm h}E}$), and those of the auto-power spectrum of the E mode, $P^{(\ell )}_{EE}(k)$, based on the E/B-mode decomposition. The IA power… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 96 publications
11
70
0
Order By: Relevance
“…Since the II+ and II− correlation functions are noisier than the GI correlation function, as is known for the ΛCDM case, it is harder to see the difference in the II correlation. Nevertheless, for the monopole and quadrupole one can see the same trend that the amplitude in 𝑓 (𝑅) gravity is smaller than that in ΛCDM, due to the fact that the amplitude of IA, often characterized by 𝑏 𝐾 (see equation 7), is positively correlated with the halo bias (Akitsu et al 2021;Kurita et al 2021); more massive halos tend to be more strongly aligned with the large-scale structure.…”
Section: Correlation Function Measurementsmentioning
confidence: 77%
See 1 more Smart Citation
“…Since the II+ and II− correlation functions are noisier than the GI correlation function, as is known for the ΛCDM case, it is harder to see the difference in the II correlation. Nevertheless, for the monopole and quadrupole one can see the same trend that the amplitude in 𝑓 (𝑅) gravity is smaller than that in ΛCDM, due to the fact that the amplitude of IA, often characterized by 𝑏 𝐾 (see equation 7), is positively correlated with the halo bias (Akitsu et al 2021;Kurita et al 2021); more massive halos tend to be more strongly aligned with the large-scale structure.…”
Section: Correlation Function Measurementsmentioning
confidence: 77%
“…Intrinsic alignment (IA) of galaxy shapes, originally focused as a contaminant to gravitational lensing signals (Croft & Metzler 2000;Heavens et al 2000;Hirata & Seljak 2004;Mandelbaum et al 2006;Hirata et al 2007;Blazek et al 2011;Troxel & Ishak 2015;Tonegawa & Okumura 2021), has been drawing attention as a new dynamical and geometric probe of cosmology (e.g., Chisari & Dvorkin 2013;Okumura et al 2019;Kurita et al 2021;Reischke et al 2021;Okumura & Taruya 2021). However, such a possibility has been explored merely by forecast studies or numerical simulations based on the ΛCDM model.…”
Section: Introductionmentioning
confidence: 99%
“…1), showing that the new method gives a larger σ ∼ 0.4 than that of the usual method, σ ∼ 0.3 as shown in Shi et al (2021). The IA power spectrum between matter density field δ m and E-mode shear field γ E is estimated following the method in Kurita et al (2021):…”
Section: An Aperture Shape Estimator For Elgsmentioning
confidence: 98%
“…To do this we use star-forming galaxies simulated in the IllustrisTNG (Springel et al 2018). We use our method to characterize shapes of the galaxies, and then measure the IA power spectrum based on the method in Kurita et al (2021) (also see Shi et al 2021). To make the realistic predictions, we take into account observational effects (sky background, filter transmission and seeing) when characterizing the galaxy shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the parameter A IA generally depends on properties of the given galaxy population as well as redshift. The analysis of numerical simulations, however, demonstrated that for fixed galaxy/halo properties, A IA is nearly redshift-independent [102]. We thus treat A IA as a constant throughout this paper.…”
Section: Density Velocity and Ellipticity Fieldsmentioning
confidence: 99%